Simultaneous control of three degrees of freedom in perfect vector vortex beams based on metasurfaces - Li Siyang; Zheng Yaqin; Zhou Changda; He Guoli; Shi Zhonghong; Li Haoyang; Zhou Zhang-Kai (Nanophotonics)
The perfect vector vortex beams (PVVBs) have played an important role in various fields due to their advantages of unique vortex features, flexible polarization distribution and multiple degrees of freedom (DoFs). The simultaneous and precise control over multiple DoFs, such as the polarization distribution, beam shape and position which greatly influence various characteristics of PVVBs, holds paramount importance. However, it is still difficult to manipulate various DoFs in a multiplexing way and the control precision of polarization distribution only reaches the half-integer level, notably hindering the further application and development of PVVBs. Here, an approach that integrates holographic technique with geometric phase metasurfaces, experimentally demonstrates the multiplexing control of PVVBs over three DoFs, i.e., enabling the independent manipulation of non-uniform polarization distributions, beam shapes and spatial positions. Furthermore, non-integer polarization order of the generated PVVBs can be arbitrary non-integer numbers with a high resolution of 0.1, largely improving the control precision. With such multiplexing manipulation of PVVBs with high precision, we can provide abundant processing dimensions for information science and technologies, exhibiting broad application potentials in fields such as information encryption, high-speed optical communication, and precise particle manipulation.